Inventory Optimization through FP-Growth-Based Association Rule Mining of Material Stock Usage Patterns - Ubaidillah, Ubaidillah; Sumiati, Sumiati (Forum Kerjasama Pendidikan Tinggi, 2025)
This research focuses on analyzing the usage patterns of material stock at PT Baruna Energi Solusindo Teknik using Association Rule Mining (ARM) with the FP-Growth algorithm. The company often experiences material shortages or excess inventory due to manual and inaccurate stock planning. To address this issue, the study aims to discover frequent itemsets and association rules among materials used in water purification installations, enabling more data-driven procurement decisions. The research employs secondary data on material usage transactions from April 2024 to March 2025, which is processed using RapidMiner software. The FP-Growth algorithm identifies material combinations with high support and confidence values. For instance, Membrane RO has a support value of 75.9%, indicating that it is used in over three-quarters of all projects. Additionally, the combination Membrane RO, PVC Pipe 1" → SDL PVC 1